Consumption of Fructose Rich Industrialized Beverages in Patients with Biopsy-Proven Non-alcoholic Fatty Liver Disease: a Cross-Sectional Study - Alves Couto, Claudia; Geyza Nogueira de Almeida, Armiliato; Mateus Jorge et al., Nardelli (Nutrición Clínica y Dietética Hospitalaria, 2020)
Introduction: Non-alcoholic fatty liver disease (NAFLD) ranges from simple steatosis to nonalcoholic steatohepatitis (NASH) and liver fibrosis. Recently, consumption of high fructose corn syrup (HFCS) has been associated with NAFLD development. Objective: The aim of this study was to investigate the relationship between consumption of HFCS and NAFLD associated metabolic factors and disease progression. Methods: This cross-sectional study included 51 patients with biopsy-proven NAFLD who underwent biochemical tests, anthropometrical assessment and full-day dietary evaluation including industrialized beverages quantification. Results: Individuals were 80% female, with 54 ± 12 years old, 96% with central obesity, 75% with insulin resistance or diabetes mellitus and were separated according to industrialized beverage intake: < 7 and ≥ 7 coups/week (i.e., daily). Daily consumption of HFCS was associated with obesity (P = 0.04), hypertriglyceridemia (P = 0.05), higher serum triglycerides (P = 0.03) and VLDL (P = 0.01). There was a significant correlation (R = 0.29; P = 0.04) between consumption of industrialized beverages and increased serum triglycerides. We found no association between daily HFCS intake and NASH diagnosis or presence of fibrosis. Conclusion: Excessive consumption of HFCS in industrialized beverages was associated with obesity, hypertriglyceridemia and high levels of blood triglycerides in patients with NAFLD.